2004
DOI: 10.1159/000077390
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Dysrhythmic Effects of Long-Pulse Gastric Electrical Stimulation in Dogs

Abstract: Background/Aim: The aim of this study was to investigate the anti-dysrhythmic effect of long-pulse gastric electrical stimulation (GES) in dogs. Methods: The study was performed in 7 healthy dogs implanted with 4 pairs of serosal gastric electrodes. Each dog was studied in three sessions on 3 separate days in a randomized order with recordings of gastric slow waves. In session 1 or 2, infusion of either saline or glucagon (0.1 U/kg in 20 ml saline instilled in 40 min) was given during the 2nd and 3rd 20-min pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…GES with long pulse/low frequency was reported to normalize vasopressin-or glucagon-induced gastric dysrhythmia and slow wave uncoupling in dogs and dysrhythmia in a rodent model of diabetes. [33][34][35][36] Normalization of dysrhythmia was also reported in patients with gastroparesis and postsurgical patients using the same method of GES. 37,38 While the exact mechanisms involved in the normalization of gastric dysrhythmia with long pulse/low frequency GES are unclear, it is known that it does not involve the vagal or cholinergic pathway.…”
Section: Alterations Of Gastric Slow Wavesmentioning
confidence: 69%
See 1 more Smart Citation
“…GES with long pulse/low frequency was reported to normalize vasopressin-or glucagon-induced gastric dysrhythmia and slow wave uncoupling in dogs and dysrhythmia in a rodent model of diabetes. [33][34][35][36] Normalization of dysrhythmia was also reported in patients with gastroparesis and postsurgical patients using the same method of GES. 37,38 While the exact mechanisms involved in the normalization of gastric dysrhythmia with long pulse/low frequency GES are unclear, it is known that it does not involve the vagal or cholinergic pathway.…”
Section: Alterations Of Gastric Slow Wavesmentioning
confidence: 69%
“…It was found that GES with long pulses was capable of normalizing gastric dysrhythmia, improving gastric emptying and reducing gastroparetic symptoms. 37 The improvement in gastric slow waves and gastric emptying was supported by the controlled animal studies, 29,[33][34][35][36] whereas, the improvement in symptoms was not demonstrated in the canine studies. 36 It was therefore, unclear whether the improvement in gastroparetic symptoms was attributable to the direct effects of GES or to the overall improvement in clinical profile of the patients.…”
Section: Ges With Long Pulsesmentioning
confidence: 97%
“…Nine healthy female hound dogs (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) were used in the study. After an overnight fast, a surgical procedure was performed on each dog under anesthesia.…”
Section: Animalsmentioning
confidence: 99%
“…These include long-pulse stimulation (pulse width in milliseconds), shortpulse stimulation (pulse width in microseconds) and stimulation with trains of pulses instead of repetitive single pulses. It seems that gastric electrical stimulation (GES) with long pulses is capable of normalizing gastric dysrhythmia and pacing gastric slow waves [12][13][14][15][16], whereas stimulation with short pulses is able to reduce nausea and vomiting [17][18][19][20][21].Several studies have shown that GES using an implantable device, called the Enterra Ò Therapy, produces a significant and sustained improvement in symptoms of vomiting and nausea and in nutritional status in most patients with intractable symptomatic gastroparesis or drug-refractory diabetes [18,19,[22][23][24].However, it is unknown whether this special method of GES is effective in reducing chemotherapy-induced emetic symptoms.…”
Section: Introductionmentioning
confidence: 99%